Investigation of crosstalk and BER in multicore fiber optic transmission link for Space Division Multiplexing - Ajay Kumar Vyas; Achyutesh Dixit; Subhashish Tiwari; Narendra Khatri (Results in Optics, 2022)
The explosive growth of optical communication (i.e., 6G or beyond 5G) will transform the way of communication. Advanced modulation schemes, guided media, high data rate, minimum dispersion, low transmission noise, and signal processing techniques are available to enrich optical networks. The multicore fiber (MCF) will play a significant role in spatial division multiplexing. The major bottleneck of the MCF is the crosstalk in different cores. This article analyzed the crosstalk in multicore fiber (i.e., 2, 3, 4, and five core) as a transmission length function and compared the Q factor, bit error rate, and output power by considering all nonlinearities of the fiber. Maximum BER obtained for 5, 4, 3, and 2 core MCF is 10-14, whereas minimum BER for 5, 4,3, and 2 core MCF are 10–248, 10–248, 10–281, and 10–242, respectively. Maximum crosstalk occurs for 5 core MCF i.e.3166.32 dBm and minimum for 2 core MCF i.e. −44.083dBm. The highest Q factor is obtained at 35.8 for 3 core 10 km, and the minimum Q factor is ∼ 7.351 for 5 core MCF.